Cost-effectiveness comparison between caudal block and intravenous ketorolac as an early post-operative analgesic in pediatric patients underwent surgery below umbilicus segment - Djayanti Sari, Juni Kurniawaty Muhdar Abubakar (Universitas Gadjah Mada, 2014)
Post-operative pain treatment in pediatric is frequently inadequate that could lead to psychological,physiological and behavioral changes. Therefore, adequate pediatric pain management is needed.Some analgesics such as ketorolac and regional anesthesia techniques such as caudal blockhave been applied to relieve pain. Ketorolac and caudal block have its own advantages anddisadvantages. The aim of study was to compare the cost-effectiveness of ketorolac and caudalblok as a post-operative analgesic in pediatric. This was double blind randomized controlledclinical trial with parallel design conducted in Dr. Sardjito General Hospital. The subjects werechildren who underwent surgery below umbilicus segment. Seventy patients were randomlydivided into two groups with 35 patients in each group. Group I (Caudal block Group) was givencaudal block with bupivacaine 0.12% 1 mL/kg body weight (BW) whereas Group II (KetorolacGroup) was given ketorolac 0.5 mg/kg BW intravenously (IV). The patientâs pain was scored at 0,15, 30, 45 minute and 1, 2, 3 hours after the conscious patients using modified ChildrenâsHospital of Eastern Ontario Pain Scale (mCHEOPS). Furthermore, the cost-effectiveness theboth interventions was also compared. The caudal block was more effective in reducing painthan the ketorolac at minutes 0 (27/8 vs 10/25) and 15 (34/1 vs 18/17) (p<0.05). However, atthird hour the ketorolac revealed more effective than the caudal block (29/6 vs 32/3) (p<0.05).The cost of the caudal block was higher than the ketorolac (IDR 95.860 Â± 5.745 vs IDR 7.200Â± 14.886) (p <0.05). However, the length of stay after the caudal block was shorter than theketorolac (40.43 Â± 13.899 vs 48.57 Â± 14.068) (p <0.05). Morphine was more needed forrescue analgesic in the ketorolac (p < 0.05) in first hour of operation, whereas after three houroperation paracetamol was more needed in caudal block (p < 0.05). In conclusion, the caudalblock is not more cost-effective than ketorolac in reducing post-operative pain in pediatricpatients underwent surgery below umbilicus segment.